Synthesis and characterization of groundnut shell carbon nanosheets for treating greywater: A step towards a circular economy - Chidambaram, P P; Ramalingam, K; Rakesh, S S; Raja, K; Ramesh, P T; Prabakaran, C; Teja, M (Plant Science Today, 2025)
Carbon nanostructured materials, such as nanosheets, can be synthetically produced from various natural waste sources through carbonization and activation. Potassium hydroxide (KOH) is a well-known agent for creating porous structures and refining the micro or nanostructure of carbon. This study explores the effect of KOH, in both its solute and solid forms, on the production of carbon from groundnut shells. Using KOH activation and thermal treatment, carbon nanosheets were synthesized from groundnut shells. The surface microstructure and individual carbon nanosheets showed significant changes when treated with solute KOH compared to solid KOH. This highlights that treatment with solute KOH is an efficient and cost-effective method for carbon nanosheet production. A column study revealed that using groundnut shell carbon nanosheets (GSCNS) to treat sewage wastewater resulted in a reduction in BOD (biochemical oxygen demand) from 393 mg L-1 to 112.23 mg L-1 (71.5%) and COD (chemical oxygen demand) from 512.70 mg L-1 to 125 mg L-1 (75.6%). Additionally, groundnut shell-derived carbon nanosheets (GSCN) treatment led to a 40-60% reduction in the cations and anions in sewage wastewater. This study emphasizes the effective utilization of groundnut shell-derived carbon nanosheets as an eco-friendly and cost-effective solution for wastewater treatment, addressing the environmental challenges of untreated sewage discharge in underdeveloped and developing regions.